A meta-cognitive approach to doping in sports: The effects of thought validation on attitudes related to doping - Horcajo, J.; Santos, D.; Guyer, J. J.; Mateos, R. (Journal of Sports Sciences, 2020)
To better understand doping-related attitude change, it is important to consider not only the amount of thinking (i.e., elaboration) done by message recipients, but also the favourability of their thoughts in response to the proposal, as well as the perceived validity in their thoughts. The main goal of the present study was to analyse the effects of a meta-cognitive process (i.e., thought validation) on attitudes related to doping. Thus, we randomly assigned participants to read a message either against or in favour of legalising several doping behaviours. Participants listed their thoughts regarding the proposal and indicated the perceived validity in their thoughts, then reported their attitudes. As hypothesised, the message against legalisation elicited more unfavourable thoughts and attitudes than the message in favour of legalisation. Most relevantly, the effects of the message direction on attitudes were greater for participants with higher (vs. lower) levels of thought validity. Furthermore, consistent with the thought validation process, results revealed that thought favourability was a better predictor of attitudes for participants with higher (vs. lower) perceived thought validity, indicating that perceiving one`s thoughts as valid plays an important role in persuasion. These findings provide novel insights for research and interventions regarding doping in sports.